1955
DOI: 10.1017/s0031182000027438
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to the genus Paradilepis Hsü, 1935

Abstract: The genus Paradilepis Hsü, 1935 syn. Meggittiella Lopez-Neyra, 1942, is defined as follows (Hsü, 1935, p. 536): ‘Dilepididae. Rostellum armed with a double crown of hooks. External segmentation little marked. Genital pores unilateral. Genital ducts pass dorsal to excretory vessels and to nerve. Testes few in number, situated to either side of the female glands. Uterus sacciform, little lobed. Parasites of birds.’

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

1961
1961
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…While epiphyseal thickenings are clearly a distinctive feature of some gryporhynchid genera (e.g. Cyclustera and Glossocercus ; Scholz & Salgado-Maldonado, 2001; Scholz et al , 2002) they are illustrated only sporadically in the literature for Paradilepis (Baer & Bona, 1960; McLaughlin, 1974; Scholz & Salgado-Maldonado, 2001; Scholz et al , 2002) and mentioned in the text on only one occasion (the ‘flattened, rounded appendages’ of Mahon, 1955). This is undoubtedly because, in this genus, the thickenings are very fine and difficult to observe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While epiphyseal thickenings are clearly a distinctive feature of some gryporhynchid genera (e.g. Cyclustera and Glossocercus ; Scholz & Salgado-Maldonado, 2001; Scholz et al , 2002) they are illustrated only sporadically in the literature for Paradilepis (Baer & Bona, 1960; McLaughlin, 1974; Scholz & Salgado-Maldonado, 2001; Scholz et al , 2002) and mentioned in the text on only one occasion (the ‘flattened, rounded appendages’ of Mahon, 1955). This is undoubtedly because, in this genus, the thickenings are very fine and difficult to observe.…”
Section: Discussionmentioning
confidence: 99%
“…Adult cestodes of the genus Paradilepis are almost entirely confined to pelicaniform birds, in many cases cormorants (Freeman, 1954; Mahon, 1955; Clark, 1957). Species have also been reported from other pelicaniform (spoonbills, pelicans, ibis, herons) and accipitriform (kites and osprey) hosts (Mayhew, 1925; Freeman, 1954; Mahon, 1955; Khalil, 1961; McLaughlin, 1974; Ryzhikov et al , 1985; Ortega-Olivares et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mais pourvus d'un rostre à deux couronnes de crochets parfois dissemblables, d'un vas deferens long et contourné, dépourvus par contre de vésicule séminale externe, ils ne répondent pas à la définition de la famille précitée, mais à celle des Dilépididés et au genre Paradilepis Hsu, 1935. Successivement, Joyeux et Baer, 1950, Neiland, 1952, Freeman, 1954, Mahon, 1955, Baer et Bona, 1958-1960, Mathevossian, 1959 ont fait le point de ces inexactitudes et les ont corri gées : Oligorchis burnamensis Johri, 1941 (1), O. hierticos Johri, 1934(2), O. longivaginosus Mayhew, 1925, O. yorkei (Kotlan, 1923 Baer, 1925, et O. strangulatus Fuhrm., 1906 (Meggitt, 1927).…”
Section: Discussionunclassified
“…These are : P. scolecina (Rudolphi, 1819) ; P. urceus (Wedl, 1855) ; and P. minima (Goss, 1914). Mahon, 1955, as a synonym of P. scolecina. Clark (1957), disagreed with Mahon and showed that the material examined by Goss contained two species one of which is identified as P. scolecina, and the other as P. minima.…”
Section: Discussionmentioning
confidence: 99%